A New Patient of Chanarin Dorfman Syndrome in Egypt - kabbany, Zeinab el; khalifa, Ola; Wafeeq, Asmaa; Ramzan, Khushnooda; Baik, Lina Al; Imtiaz, Faiqa; Wageeh, Yasser; Zalata, Khaled; Mousa, Alaa (Archives of Clinical and Medical Case Reports, 2019)
Chanarin Dorfman syndrome (CDS) is an autosomal recessive neutral lipid storage disorder characterized by ichthyosis, and multisystem affection. Here, we report another patient from Egypt. The clinical data from a patient and his family were collected. DNA was isolated from peripheral blood leukocytes. Coding exons and the flanking introns of ABHD5 gene were PCR amplified, purified, and sequenced. Our patient meets the major clinical symptoms of CDS. Direct sequencing of ABHD5 gene led to the identification of a homozygous single nucleotide change (c.700C>T) in our patient. The parents were both heterozygous carriers, while his sister was wild type normal for the identified variant. In conclusion, these results indicate that p.Arg234Ter is a pathogenic mutation associated with the Chanarin-Dorfman syndrome in our patient in this study.